Composition-controlled degradation behavior of macroporous scaffolds from three-armed biodegradable macromers. (January 2022) - Krieghoff, Jan; Kascholke, Christian; Loth, Rudi; Starke, Annett; Koenig, Andreas; Schulz-Siegmund, Michaela; Hacker, Michael C.
Highlights: Synthesis of three-armed macromers with a range of biodegradable building blocks and degrees of end group methacrylation. Macromers contain oligolactide building blocks with adjustable glycolide incorporation. Fabricated macromer-based macroporous scaffolds show degradation with continuous mass loss and only mild pH decrease. Degradation rate dependent on macromer hydrophilicity (core, glycolic acid content), molecular weight and composition. Abstract: Acidification of implant microenvironment and inflammation due to degradation products of high molecular weight poly(α‑hydroxy acids) like PLA and PLGA is a risk that can limit their use in regenerative medicine, tissue engineering and drug delivery. We developed macromers that consist of a three-armed core with varying degrees of ethoxylation, hydrolytically degradable oligolactide blocks and terminal methacrylate groups (TriLA macromers) for cross-polymerization into monolithic or macroporous structures. Within the macromer platform, biophysical and biochemical properties can be adjusted by macromer chemistry. In this work, eight new macromer types with a reduced degree of methacrylation or substitution of a fraction of the lactic acid units with glycolic acid were successfully synthesized starting from a fully methacrylated, oligolactide-based TriLA macromer. Chemical characterization confirmed feed-dependent glycolic acid integration and controlled reduction in degree of methacrylation. The degradation behavior of macroporous scaffolds made by solid lipid templating from both the previously established and the new macromers was systematically investigated. In general, the scaffolds displayed continuous mass loss over time when the onset time of degradation was passed. Depending on arm length as well as hydrophilicity of the oligomeric building blocks, degradation half-life ranged from 3 to 4 weeks to over 81 weeks. Glycolic acid integration accelerated network degradation more effectively than an increase in core molecule hydrophilicity. The observed, adjustable degradation profiles with only moderate medium acidification and a dominant phase of almost linear mass loss make this material platform promising for regenerative and drug delivery applications. Graphical abstract: Image, graphical abstract